A sub-national real-time epidemiological and vaccination database for the COVID-19 pandemic in Canada - Isha Berry (Nature Portfolio, 2021)
Measurement(s) COVID-19 Cases • COVID-19 Mortalities • COVID-19 vaccination Technology Type(s) digital curation Sample Characteristic - Organism Homo sapiens Sample Characteristic - Location Canada Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14331311